Freedom of religion and religious pluralism - Bhuiyan, Jahid Hossain; Zoethout, Carla M. (Studies in religion, secular beliefs and human rights, 2023)
Religious pluralism is an important aspiration of contemporary societies, meaning that religious diversity is permitted and everyone has the freedom of religion or belief, or not to believe. The peaceful coexistence of people of a myriad of faiths is indispensable for securing peace in the modern era of political upheaval and economic dissonance. This book brings together a variety of religious and non-religious perspectives on religious pluralism. It explores the key philosophical and legal issues associated with religious freedom and social harmony. Freedom of Religion and Religious Pluralism intends to serve as a valuable resource for scholars specialising in religion, citizenship, and migration studies. It will also act as a reference for courses on law, religion, and human rights